Epidemiology and healthcare factors associated with neonatal enterococcal infections. Issue 5 (13th September 2019) - Wang, Joanna; Kortsalioudaki, Christina; Heath, Paul T; Buttery, Jim; Clarke, Paul; Gkentzi, Despoina; Anthony, Mark; Tan, Kenneth
Abstract : Objective: To investigate the epidemiology and healthcare factors associated with late-onset neonatal enterococcal infections. Design: Multicentre, multinational retrospective cohort study using prospectively collected infection data from a neonatal infection surveillance network between 2004 and 2016; this was supplemented with healthcare data from a questionnaire distributed to participating neonatal units. Setting: Sixty neonatal units across Europe (UK, Greece, Estonia) and Australia. Patients: Infants admitted to participating neonatal units who had a positive culture of blood, cerebrospinal fluid or urine after 48 hours of life. Results: In total, 414 episodes of invasive Enterococcus spp infection were reported in 388 infants (10.1% of a total 4083 episodes in 3602 infants). Enterococcus spp were the second most common cause of late-onset infection after coagulase-negative Staphylococcus spp and were strongly associated with necrotising enterocolitis (NEC) (adjusted OR 1.44, 95% CI 1.02 to 2.03, p=0.038), total parenteral nutrition (TPN) (adjusted OR 1.34, 95% CI 1.06 to 1.70, p=0.016), increasing postnatal age (per 1-week increase: adjusted OR 1.04, 95% CI 1.02 to 1.06, p<0.001) and decreasing birth weight (per 1 kg increase: adjusted OR 0.85, 95% CI 0.74 to 0.97, p=0.017). There was no evidence that inadequate nurse to patient staffing ratios in high-dependency units were associated with a higher risk of enterococcal infections. Conclusions: Enterococcus spp were the second most frequent cause of late-onset infections. The association between enterococcal infections, NEC and TPN may inform empiric antimicrobial regimens in these contexts and provide insights into reducing these infections.